A MODEL OF DELIBERATIVE AND AGGREGATIVE DEMOCRACY. (19th February 2015) - Perote-Peña, Juan; Piggins, Ashley
Abstract: We present a model of collective decision making in which aggregation and deliberation are treated simultaneously. Individuals debate in a public forum and potentially revise their judgements in light of deliberation. Once this process is exhausted, a rule is applied to aggregate post-deliberation judgements in order to make a social choice. Restricting attention to three alternatives, we identify conditions under which a democracy is 'truth-revealing'. This condition says that the deliberation path and the aggregation rule always lead to the correct social choice being made, irrespective of both the original profile of judgements and the size of the electorate.